Runaway College Costs : How College Governing Boards Fail to Protect Their Students - Koch, James V., 1942-; Cebula, Richard J. (Book collections on Project MUSE., 2020)
"This book, written by two economists, argues that those who sit on boards of trustees for public universities have not used their political clout to counteract the trend toward decreased state funding of higher education and consequent increases in tuition. Instead trustees have voted overwhelmingly in favor of tuition hikes. The authors make suggestions for what boards can do to mitigate rising costs"--